Long-term outcomes on spatial hearing, speech recognition and receptive vocabulary after sequential bilateral cochlear implantation in children. (January 2015) - Sparreboom, Marloes; Langereis, Margreet C.; Snik, Ad F.M.; Mylanus, Emmanuel A.M.
Highlights: In the long-term, children with BiCIs still show improvements is spatial acuity. Spatial acuity for ILD cues is higher than for ITD cues. Speech recognition in quiet and noise is better with BiCIs than with a UCI. Children with sequential BiCIs show a bilateral benefit on receptive vocabulary. Mainstream education and BiCIs lead to an age-appropriate receptive vocabulary. Abstract: Sequential bilateral cochlear implantation in profoundly deaf children often leads to primary advantages in spatial hearing and speech recognition. It is not yet known how these children develop in the long-term and if these primary advantages will also lead to secondary advantages, e.g. in better language skills. The aim of the present longitudinal cohort study was to assess the long-term effects of sequential bilateral cochlear implantation in children on spatial hearing, speech recognition in quiet and in noise and receptive vocabulary. Twenty-four children with bilateral cochlear implants (BiCIs) were tested 5–6 years after sequential bilateral cochlear implantation. These children received their second implant between 2.4 and 8.5 years of age. Speech and language data were also gathered in a matched reference group of 26 children with a unilateral cochlear implant (UCI). Spatial hearing was assessed with a minimum audible angle (MAA) task with different stimulus types to gain global insight into the effective use of interaural level difference (ILD) and interaural timing difference (ITD) cues. In the long-term, children still showed improvements in spatial acuity. Spatial acuity was highest for ILD cues compared to ITD cues. For speech recognition in quiet and noise, and receptive vocabulary, children with BiCIs had significant higher scores than children with a UCI. Results also indicate that attending a mainstream school has a significant positive effect on speech recognition and receptive vocabulary compared to attending a school for the deaf. Despite of a period of unilateral deafness, children with BiCIs, participating in mainstream education obtained age-appropriate language scores.